Hypercontractile cardiac phenotype in mice overexpressing the regulatory subunit PR72 of protein phosphatase 2A - Herting, Julius R.; König, Jule H.; Hadova, Katarina; Heinick, Alexander; Müller, Frank U.; Pauls, Paul; Seidl, Matthias D.; Soppa, Carolina; Kirchhefer, Uwe (Frontiers in Cardiovascular Medicine, 2023)
Background The activity, localization, and substrate specificity of the protein phosphatase 2A (PP2A) heterotrimer are controlled by various regulatory B subunits. PR72 belongs to the B'' gene family and has been shown to be upregulated in human heart failure. However, little is known about the functions of PR72 in the myocardium. Methods To address this issue, we generated a transgenic mouse model with heart-specific overexpression of PP2A-PR72. Biochemical and physiological methods were used to determine contractility, Ca2+ cycling parameters, and protein phosphorylation. Results A 2.5-fold increase in PR72 expression resulted in moderate cardiac hypertrophy. Maximal ventricular pressure was increased in catheterized transgenic mice (TG) compared to wild-type (WT) littermates. This was accompanied by an increased shortening of sarcomere length and faster relaxation at the single-cell level in TG. In parallel with these findings, the peak amplitude of Ca2+ transients was increased, and the decay in intracellular Ca2+ levels was shortened in TG compared to WT. The changes in Ca2+ cycling in TG were also evident from an increase in the full duration and width at half maximum of Ca2+ sparks. Consistent with the contractile data, phosphorylation of phospholamban at threonine-17 was higher in TG hearts. The lower expression of the Na+/Ca2+ exchanger may also contribute to the hypercontractile state in transgenic myocardium. Conclusion Our results suggest that PP2A-PR72 plays an important role in regulating cardiac contractile function and Ca2+ cycling, indicating that the upregulation of PR72 in heart failure is an attempt to compensate functionally.